2016
DOI: 10.1111/acem.13048
|View full text |Cite
|
Sign up to set email alerts
|

Which Febrile Children With Sickle Cell Disease Need a Chest X‐Ray?

Abstract: Objective Controversy exists regarding which febrile children with sickle cell disease (SCD) should receive a chest x‐ray (CXR). Our goal is to provide data informing the decision of which febrile children with SCD presenting to the emergency department (ED) require a CXR to evaluate for acute chest syndrome (ACS). Methods Retrospective chart review of children ages 3 months to 21 years with SCD presenting to the ED at one of two academic children's hospitals with fever ≥38.5°C between January 1, 2010, and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
4
6
0
Order By: Relevance
“…When applying the tool to this cohort, the total number of CXRs performed would have been reduced by 63% ( n = 576), although this would be at the expense of missing 22 clinically significant CXRs (8·5%). This fits in with findings by Eisenbrown et al ., 27 who found that 98% of ACS cases could be identified when obtaining a CXR in children with NHLBI criteria, chest pain, ACS history or those with a WCC 18·75. The tool we propose has the potential to identify not only ACS but other clinically significant CXR findings, and to importantly reduce unnecessary CXRs.…”
Section: Discussionsupporting
confidence: 91%
“…When applying the tool to this cohort, the total number of CXRs performed would have been reduced by 63% ( n = 576), although this would be at the expense of missing 22 clinically significant CXRs (8·5%). This fits in with findings by Eisenbrown et al ., 27 who found that 98% of ACS cases could be identified when obtaining a CXR in children with NHLBI criteria, chest pain, ACS history or those with a WCC 18·75. The tool we propose has the potential to identify not only ACS but other clinically significant CXR findings, and to importantly reduce unnecessary CXRs.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies had previously reported different predictors of bacteremia and other severe infections in patients with SCD, including elevated CRP, procalcitonin, WBC and neutrophils, toxic appearance, vomiting and long-term CVC 2,4,8,9 . IL-6 has also been recently described by our group as a marker of CSBI in these patients 6 .Other studies had also reported hipoxemia and elevated WBC or neutrophils as predictors of pneumonia or ACS 3,10 .…”
Section: Discussionsupporting
confidence: 61%
“…This finding is consistent with several studies. 24 , 25 Eisenbrown et al 25 reported that a higher WBC level in SCD patients with a cough should prompt a chest X-ray.…”
Section: Discussionmentioning
confidence: 99%